Do not disturb - Lew, Trisha (Nanyang Technological University, 2024)
Do Not Disturb (2024) speaks of the tension between us and our built environment, and is a point of reflection into how our spaces are built—the purposes they serve, its successes, its failures, and how our future must understand the balance of order and the needs of the people. Through research findings and the artistic mediums of interactive media, generative AI, and graphic design, this work serves as a contribution to the ongoing discourse surrounding the dialogue between society and hostile architecture, calling for future consideration of human-centric design in our urban spaces.